Marvel's iron man 3 prelude ebook - Gage, Christos (Marvel Worldwide, Inc., 2015)
Collects Marvel's Iron Man 2 Adaptation #1-2; Marvel's Iron Man 3 Prelude #1-2, Iron Man (2005) #1. The Marvel Cinematic Universe returns! First, it's the comics adaptation of the blockbuster film Iron Man 2! Why is the U.S. government going after Iron Man? Plus, a mysterious figure from Tony's past returns - and he's got a vendetta. Featuring the first appearance and origin of War Machine! Then, it's an all-new story set between the events of Marvel's the Avengers and the upcoming Iron Man 3! What mysterious project has Tony Stark been developing since his alliance with SHIELD and his joining Earth's Mightiest Heroes? And how will it change the way he lives ... forever?